FRACTIONAL TIME-TEMPERATURE SUPERPOSITION MODEL OF VISCOELASTIC MATERIAL WITH VERTICAL SHIFT FACTOR - WANG Yao; SUN DaGang; LI ZhanLong; QIN Yuan; REN GuoXiang (Jixie qiangdu)
The dynamic properties of the viscoelastic material have remarkable temperature-frequency effect. In order to characterize the dynamic properties of the viscoelastic material more precision,on the basis of the fractional constitutive model and the time-temperature superposition principle,the fractional time-temperature superposition model of the viscoelastic material with vertical factor（ VFTTS） was proposed. The DMA test was conducted on the viscoelastic material used in vibration control of engineering vehicle. The dynamic behaviors（ storage modulus,loss modulus and loss factor） under variable temperatures（-75℃ ～ 65℃） and frequencies（ 0. 5 Hz,1 Hz,2 Hz,3. 3 Hz,5 Hz and 10 Hz） were analyzed. Meanwhile,the master curves of the storage modulus at the reference temperature 5℃ are obtained by the VFTTS model and the FTTS model（ only with horizon factor）. The fractional standard linear solid model（ CFSLS） was used to validate the accuracy of the above two models. The results show that the prediction ranges of the frequencies of VFTTS model and FTTS model are the same. The superhigh frequency predictions between 1. 086 × 10-8 Hz and 1. 240 × 1011 Hz are realized. The relative errors of the two models are 6. 07% and13. 22%. In summary,the VFTTS model has broad prediction ability and higher accuracy.